ENTREPRENEURSHIP AS AN INSTRUMENT OF REGIONAL DEVELOPMENT: MEASURING ENTREPRENEURSHIP ECOSYSTEM IN TURKEY - Oguztimur, Senay; Seckin, Ebru (MEHMET AKIF ERSOY UNIV, 2018)
Starting from 1970s, flexible specialization, development in information and communication technology and innovativeness, allowed SME's empowered. On the other hand, taking steps to reveal the regions' endogenous dynamics increased the significance of entrepreneurship and made it one of the basic factors. In order to balance interregional development level and to boost the entrepreneurship with the inner potentials of the underdeveloped regions have started to be a part of the regional politics. In this context literature survey has done and evaluated the reasons of entrepreneurship mattered for regional development and what the environmental factors were. The four main factors affected entrepreneurship are: (I) Economic factors, (II) Human capital, (III) Physical infrastructure, (IV) Innovativeness. These four factors are normalized and generated index due to understanding Turkey's provinces entrepreneurship level. As a result, it is aimed to contribute the literature within secondary sources for the context of Eastern Blacksea Region.
Keywords: Endogenous regional development; entrepreneurship; Turkey; COMPETITIVENESS; CITIES; Business & Economics